If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + -5 = 6 Reorder the terms: -5 + 3m = 6 Solving -5 + 3m = 6 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3m = 6 + 5 Combine like terms: -5 + 5 = 0 0 + 3m = 6 + 5 3m = 6 + 5 Combine like terms: 6 + 5 = 11 3m = 11 Divide each side by '3'. m = 3.666666667 Simplifying m = 3.666666667
| x^3+18x-8=0 | | 0-(3a+6b-5ab)= | | 3x+x+6x=120 | | 3a-2a=11 | | (x-3)-(x-3)(x+4)=0 | | 4[x+5]=56 | | 3.6*4.5= | | p=70 | | (6)(2t)-4th= | | 5b^2-11b-42=0 | | 18-16=19x-15 | | (37b-6)-9(4b+3)=-4 | | 19x+9+15x=45 | | (2x-1)(x-4)-(3x+2)(3x-1)= | | 6x-54=30 | | 14x^2+28x^5=0 | | X+(x+1)=20 | | 3x+-7=-1 | | -3x+-5=-11 | | 5(2-3x)-2(x-4)=3(x+2) | | 3-z=5 | | 0.3R=21 | | x+10y=122 | | 7xy(9x+7y)= | | -5(5n+2)=30 | | (y+4)(y-3)+(y-2)(y-3)= | | (4+4)(y-3)+(y-2)(y-3)= | | 162+7x-3+10x=12 | | 5-0.75x=2 | | 3y-2z=13 | | 9x-3=4x+50 | | 33x-8=55 |